Design and Build Applications for Choice of Vocational Schools Using the Simple Additive Weighting Method - Sisrayanti; Rizal, Fahmi; Ambiyar (The Indonesian Journal of Computer Science, 2024)
The fact that the problem of incompatibility of majors and educational backgrounds of students is one of the factors in the problems of education in Indonesia. This is of particular concern to the world of education, including vocational education. To enter education, especially at the Vocational High School (SMK) level, students are required to choose a major according to their interests and talents. However, many students are not aware of their abilities. Consequently, the objective of this research is to develop an Android application tailored for Vocational High Schools, employing the Simple Additive Weighting technique. The methodology employed here is the Research and Development (R&D) approach utilizing the 4D development model. The outcome of this investigation yields an application that serves as a valuable tool for both educators and students in making informed decisions regarding their choice of majors in Vocational High Schools